2012
DOI: 10.1128/jcm.06855-11
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Clustering of NDM-1-Producing Klebsiella pneumoniae Sequence Type 340 Strains in Four Patients at a South Korean Tertiary Care Hospital

Abstract: cIn November 2010, NDM-1-producing Klebsiella pneumoniae (NDMKP) was identified for the first time in South Korea from four patients with no history of traveling abroad who stayed for 21 to 205 days in a tertiary care hospital. All were sequence type (ST) 340 and had nearly identical XbaI pulsed-field gel electrophoresis (PFGE) patterns. The bla NDM-1 -carrying plasmids were in the IncN group, with sizes ranging from 50 to 200 kb. These findings suggest that NDMKP had already been introduced into South Korea b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 24 publications
1
36
0
6
Order By: Relevance
“…Recently, two studies have demonstrated limited nosocomial transmission of bla NDM-1 -producing isolates in non-endemic areas. 21,37 We previously showed that the two bla NDM-1 -carrying E. coli strains (CRE396 and CRE397) in the infant and her mother were clonally related. 11 Here, we confirmed that there was in vivo transfer of the bla NDM-1 -carrying IncX3 plasmid among E. coli , K. peumoniae and E. aerogenes strains carried by the infant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies have demonstrated limited nosocomial transmission of bla NDM-1 -producing isolates in non-endemic areas. 21,37 We previously showed that the two bla NDM-1 -carrying E. coli strains (CRE396 and CRE397) in the infant and her mother were clonally related. 11 Here, we confirmed that there was in vivo transfer of the bla NDM-1 -carrying IncX3 plasmid among E. coli , K. peumoniae and E. aerogenes strains carried by the infant.…”
Section: Discussionmentioning
confidence: 99%
“…In Enterobacteriaceae , bla NDM-1 has been identified on plasmids with a narrow (IncF1B, IncFII) or broad (IncA/C, IncH, IncL/M and IncN) host range and rarely in the chromosome. 18,19,20,21 The first plasmid to be completely sequenced was pNDM-HK (IncL/M, INSDC-GenBank accession HQ451074). The other plasmids that have been completely sequenced and deposited in the INSDC-GenBank were pNDM-1_Dok01 (IncA/C2, AP012208), pNDM-KN (IncA/C2, JN157804), pNDM10505 (IncA/C2, JF503991), pNDM10469 (IncA/C2, JN861072), pNDM102337 (IncA/C2, JF714412), pMR0211 (IncA/C2, JN687470), p271A (IncN2, JF785549), pNDM-MAR (IncH1B-F1B, JN420336) and pGUE-NDM (IncFII, JQ364967).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the recent spread of NDM producers in Western Europe, North America, Australia, and the Far East has clearly been attributed to patients who originated mainly from India, Pakistan, and Bangladesh (192). A characteristic of NDM-producing K. pneumoniae isolates has so far been their rapid dissemination; indeed, infected or colonized humans without obvious connection to the Indian epidemic are increasingly being reported in several countries (125,190,214).…”
Section: Producers Of M␤lsmentioning
confidence: 99%
“…The index case was not identified, and the source of that strain in the hospital setting could not be determined. Of note, whereas there have been several reported outbreaks involving NDM-1-producing K. pneumoniae in different countries, such as Turkey (16,17), Colombia (18), Canada (19), Kenya (20), Italy (21), and South Korea (22), reports of NDM-1-producing E. coli have been scattered (13,(23)(24)(25)(26), including isolates recovered from companion animals in the United States (27). However, nosocomial transmissions of NDM-1-pro-ducing E. coli are extremely rare, with one recent report from South Korea (28).…”
Section: W Orldwide Occurrence Of Carbapenemase Producers Amongmentioning
confidence: 99%